Hubungan Pola Makan dengan Penyakit Kanker Kolorektal - Angeline, Reni; Christina, Shintia; Kertadjaya, Wiwi; Mansyur, Firman Riscky (Universitas Kristen Krida Wacana, 2025)
Cancer is the second leading cause of death globally. Colorectal cancer is one of the most common cancers worldwide. Referring to GLOBOCAN data, in general colorectal cancer is the third highest incidence of cancer after lung cancer and breast cancer. This is attributed to the diet that affects colorectal cancer. Most colorectal cancer are still closely related to genetics. In addition to genetic factors, food intake factors also closely related to colorectal cancer. Current research shows colorectal cancer occurs due to genetic mutations and inflammatory bowel disease. This literature review uses a Literature review design using a search method with a library of research articles or journals through PubMed and other journal sources. The results of the literature review are associated with dietary pattern that affect colorectal cancer, red mead intake is related to the growth of colorectal cancer, while high fiber food can help reduce the risk of colorectal cancer.